ENTERPRISE DEVELOPMENT AS A RESULT OF IMPLEMENTING ORGANIZATIONAL TRANSFORMATIONS IN MODERN CONDITIONS (Development Service Industry Management, 2024)
The topic's relevance is due to the rapid changes in the global economy, the increasing role of digital technologies, and the intensification of competition between enterprises. In the modern business environment, enterprises must adapt quickly to remain competitive and meet new market requirements. This necessitates the implementation of organizational transformations, which include changes in the structure of the enterprise, its management, business processes, and corporate culture.The article is devoted to the study of enterprise development as a result of implementing organizational transformations in modern conditions.It has been proven that the modern dynamic environment requires enterprises to adapt to new conditions constantly. Organizational transformations have become essential for maintaining competitiveness and responding to market changes.It has been established that the use of modern technologies allows for increasing the efficiency of processes, improving the quality of customer service, and creating products that meet individual needs.It is substantiated that during transformations, personnel resistance, the risk of resource loss, and problems with integrating new processes are present. However, these challenges can be reduced through leadership, team support, quality communication, and clear planning.Organizational transformations allow enterprises to develop sustainable business models that support economic, social, and environmental responsibility. This increases customer trust and strengthens the company's reputation in the market.It has been proven that transformations open prospects for enterprises to diversify products, expand their audience, and go international, allowing them to be more stable and competitive.
Keywords: business environment; innovation; competitiveness; organizational transformations; enterprise development; sustainable development; digitalization